Investigating of Middle-school Students’ Attitudes Toward Programming - Kadir Gürsoy, Erdem Çekmez (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
This study presents an investigation of the attitudes of middle school students toward computer programming after they received an instructional sequence designed to introduce computer programming. The aims of this study are to (i) determine the levels of students’ attitudes toward computer programming, (ii) determine whether students’ attitudes toward computer programming differ in terms of gender, and (iii) reveal students’ ideas about the implemented instructional content. To this aim, an instructional sequence that aimed to provide students with the necessary knowledge to use Scratch was designed and implemented in an eight-week plan. Apart from technical knowledge to use the software, the content included activities in which students were asked to create three games. The participants of the study consist of fifteen 5th grade and seventeen 6th grade students. To determine students’ attitudes toward computer programming an existing scale in the literature was used. The results of the study showed that the students developed positive attitudes toward computer programming after the instruction. Besides, it was found that there was no significant difference between boys and girls in terms of attitudes toward programming.